Fernando Amato – Christian Boyanovsky Bazán. Setentistas: de La Plata a la Casa Rosada. Buenos Aires: Sudamericana, 2008, 447 p. ISBN: 978-950-0729-109 - camacho, Omar Alonso (2009)
Fil: camacho, Omar Alonso. Universidad Nacional de Cuyo